Thiadiazoloquinoxalines - Hu, Ben-Lin; Baumgarten, Martin (Synlett, 2019)
In this account we summarized our work on the modification and extension of the thiadiazoloquinoxaline (TQ) as a strong acceptor unit for organic electronics. While also alternating conjugated copolymers with different donors were published, the focus here is the description of variation of the acceptor unit leading to many small molecules with different electronic properties as indicated from their optical absorptions, cyclic voltammetry (CV) data, density functional theory (DFT), and time-dependent (TD-DFT) calculations. The extension with ortho-diquinones seemed a promising way to enlarge the TQ molecules and further increase their electron affinity. At the end it is demonstrated how these units can be merged with other acceptors like naphthalenediimide (NDI) and be extended in an iterative way to extremely long condensed pyrene-fused heteroacenes with TQ end groups just by ring opening of the thiadiazole five-membered ring followed by further condensations in an iterative way.1 Introduction2 The Synthesis of TQ Cores3 The Extension of TQ3.1 The Extension at 4,9-Positions3.2 The Extension at 6,7-Positions3.3 The Extension on NDI3.4 The Extension with TQ for Endcapping (Bis TQ)4 Conclusions
Keywords: thiadiazoloquinoxalines; strong acceptor; benzothiadiazoles; nitrogen heterocycles; polycyclic aromatics